Outward rectification of inhibitory postsynaptic currents in cultured rat hippocampal neurones. - Barker, J L (1988)
1. Inhibitory postsynaptic potentials (IPSPs) and currents (IPSCs) were recorded from cultured hippocampal neurones of the embryonic rat at 22 degrees C, using the whole-cell patch-clamp technique with a low-Cl-, 145 mM-potassium gluconate solution in the patch pipette. Individual synaptic events were elicited at low frequency (0.05-0.1 Hz) by stimulating a presynaptic neurone either by direct intracellular current injection, or by applying a brief pulse of L-glutamate. 2. In target neurones voltage clamped at -40 mV, outwardly directed IPSCs of mean amplitude 0.23 nA were recorded. The IPSCs were depressed by the GABA antagonist bicuculline, and reversed polarity between -50 and -80 mV (mean -64 mV), as did current responses to gamma-aminobutyric acid. The IPSPs and IPSCs reversed as a single phase; no bicuculline-resistant 'late' synaptic event was observed. 3. The IPSCs had variable kinetics, with rise times between 1 and 5 ms (mean 2.9 ms) at -40 mV, and slower, monoexponential, decay phases (decay time constant, tau IPSC, 10-40 ms at -40 mV). In some cells, tau IPSC clearly increased with depolarization. 4. The IPSC reversal potential was -64 +/- 9 mV (n = 23) under the experimental conditions used; this suggests that the synaptically activated channels are approximately 25 times more permeable to Cl- than to the gluconate anion. 5. The peak conductance associated with the IPSC showed outward rectification. The synaptic conductance measured at -40 mV was 1.7 times greater than that measured at -100 mV; at -20 mV, synaptic conductance was 2.5 times greater than at -100 mV. This outward rectification can be explained by a constant field model under these experimental conditions of asymmetric Cl- concentrations.